Small GTPases in platelet membrane trafficking - Tony G. Walsh; Yong Li; Andreas Wersäll; Alastair W. Poole (Platelets, 2019)
Our understanding of fundamental biological processes within platelets is continually evolving. A critical feature of platelet biology relates to the intricate uptake, packaging and release of bioactive cargo from storage vesicles, essential in mediating a range of classical (haemostasis/thrombosis) and non-classical (regeneration/inflammation/metastasis) roles platelets assume. Pivotal to the molecular control of these vesicle trafficking events are the small GTPases of the Ras superfamily, which function as spatially distinct, molecular switches controlling essential cellular processes. Herein, we specifically focus on members of the Rab, Arf and Ras subfamilies, which comprise over 130 members and platelet proteomic datasets suggest that more than half of these are expressed in human platelets. We provide an update of current literature relating to trafficking roles for these GTPases in platelets, particularly regarding endocytic and exocytic events, but also vesicle biogenesis and provide speculative argument for roles that other related GTPases and regulatory proteins may adopt in platelets. Advances in our understanding of small GTPase function in the anucleate platelet has been hampered by the lack of specific molecular tools, but it is anticipated that this will be greatly accelerated in the years ahead and will be crucial to the identification of novel therapeutic targets controlling different platelet processes.